Magnetic resonance elastography quantification of the solid-to-fluid transition of liver tissue due to decellularization. (April 2020) - Everwien, Hannah; Ariza de Schellenberger, Angela; Haep, Nils; Tzschätzsch, Heiko; Pratschke, Johann; Sauer, Igor M.; Braun, Jürgen; Hillebrandt, Karl H.; Sack, Ingolf
Abstract: Maintenance of tissue extracellular matrix (ECM) and its biomechanical properties for tissue engineering is one of the substantial challenges in the field of decellularization and recellularization. Preservation of the organ-specific biomatrix is crucial for successful recellularization to support cell survival, proliferation, and functionality. However, understanding ECM properties with and without its inhabiting cells as well as the transition between the two states lacks appropriate test methods capable of quantifying bulk viscoelastic parameters in soft tissues. We used compact magnetic resonance elastography (MRE) with 400, 500, and 600 Hz driving frequency to investigate rat liver specimens for quantification of viscoelastic property changes resulting from decellularization. Tissue structures in native and decellularized livers were characterized by collagen and elastin quantification, histological analysis, and scanning electron microscopy. Decellularization did not affect the integrity of microanatomy and structural composition of liver ECM but was found to be associated with increases in the relative amounts of collagen by 83-fold (37.4 ± 17.5 vs. 0.5 ± 0.01 μg/mg, p = 0.0002) and elastin by approx. 3-fold (404.1 ± 139.6 vs. 151.0 ± 132.3 μg/mg, p = 0.0046). Decellularization reduced storage modulus by approx. 9-fold (from 4.9 ± 0.8 kPa to 0.5 ± 0.5 kPa, p < 0.0001) and loss modulus by approx. 7-fold (3.6 kPa to 0.5 kPa, p < 0.0001), indicating a marked loss of global tissue rigidity as well as a property shift from solid towards more fluid tissue behavior (p = 0.0097). Our results suggest that the rigidity of liver tissue is largely determined by cellular components, which are replaced by fluid-filled spaces when cells are removed. This leads to an overall increase in tissue fluidity and a viscous drag within the relatively sparse remaining ECM. Compact MRE is an excellent tool for quantifying the mechanical properties of decellularized biological tissue and a promising candidate for useful applications in tissue engineering. Graphical abstract: Image 1 Highlights: Magnetic resonance elastography was used to assess the mechanical behavior of decellularized liver compared to native liver. We could observe a shift from solid to more fluid tissue behavior after the decellularization procedure. Our data suggest that liver rigidity is mainly determined by cellular components and their interactions with the ECM.